SEPARATION, IDENTIFICATION ANO CUANTIFICATION OF TANNINS OF CALATHEA LUTEA "BIJAO" - Aguirre M., R. (2010)
We work with Calathea lutea "bijao" of Pucallpa. In the phitochemist analysis, saponines, fiavonoids, cumarines, alkaloids and phenolic compounds: catechin tannins were found. A high per cent of tannins were found, this was realized by volumetric analysis.